ANALISA BALOK PANJANG (INFINITE BEAM) DI ATAS PONDASI ELASTIS DENGAN PENDEKATAN BEDA HINGGA - Minson Simatupang (Universitas Halu Oleo, 2010)
Concept of Winkler’s foundation or modulus of sub grade reaction approach is usually used to solve the problem of beam resting on an elastic foundation. The analytical method solution for the Winkler foundation is not generally used, because the solution difficulty adapt for the changes of beam’s dimension or modulus of sub grade reaction of soil for example. For that limitation, numeric approach, among them Finite Difference Method (FDM) become appropriate choice. In this paper, FDM is examined used for the analysis of rail way resting on ballast as an infinite beam on Winkler medium. The rail way’s load comes from locomotive with passenger coach combination. Estimation of deflections and internal forces of rail, subjected to rail way’s load is done by Visual Basic Program assistance for the matrix operation. The results show that finite difference approach has high level accuracy to analytical method.